Effect of preservative removal from fixed-combination bimatoprost/timolol on intraocular pressure lowering: a potential timolol dose–response phenomenon - Shen J (Dove Medical Press, 2016)
Jie Shen,1 Marina Bejanian2 1Department of Translational Sciences, 2Department of Ophthalmology Clinical Development, Allergan plc, Irvine, CA, USA Purpose: Many patients with glaucoma require combination therapies to achieve target intraocular pressure (IOP) and preserve visual function. Ocular hypotensives often contain a preservative (eg, benzalkonium chloride [BAK]), but preservative-free (PF) formulations have been developed for patients with sensitivity. A Phase III study found the efficacy of bimatoprost 0.03%/timolol 0.5% (bim/tim, Ganfort®) PF to be equivalent to that of preserved bim/tim, although a trend favoring bim/tim PF was observed. As BAK is a corneal penetration enhancer, this literature review aims to explain these findings by exploring the relationship between timolol concentration and its IOP-lowering effect. Methods: Systematic searches were performed in Scopus and PubMed for clinical trials published in English between 1960 and July 2014 using the keywords “timolol”, “intraocular pressure”, and the concentrations “1%, 0.5%, OR 0.25%”. Articles that directly compared IOP-lowering effects of ≥2 concentrations of timolol were identified by manual screening, and cross-checked for duplication. Results: Seventeen studies that included 10–371 patients were evaluated; the majority were randomized (16/17), double-masked (14/17), and enrolled patients with open-angle glaucoma or ocular hypertension (12/17). All studies investigated timolol in preserved formulations. Timolol concentrations tested ranged from 0.008% to 1.5%. Of 13 studies comparing timolol 0.25% versus 0.5%, two found the 0.25% dose to have greater IOP-lowering effects, and three reported the opposite; eight reported similar IOP lowering. Results also indicate that timolol 0.5% may be more effective than higher concentrations. Conclusion: The evidence suggests that timolol may have an inverted U-shaped dose–response curve, and that its optimal IOP-lowering concentration is between 0.25% and 0.5%. Compared with bim/tim, removal of the permeability enhancer BAK in bim/tim PF could have resulted in a lower timolol concentration at the target site, bringing the effective concentration within the 0.25%–0.5% range and enhancing the efficacy of bim/tim PF. Keywords: glaucoma, intraocular pressure, timolol, bimatoprost, preservative, dose–response